Biogeographically distinct controls on C3 and C4 grass distributions: merging community and physiological ecology. Issue 3 (11th December 2014) - Griffith, Daniel M.; Anderson, T. Michael; Osborne, Colin P.; Strömberg, Caroline A. E.; Forrestel, Elisabeth J.; Still, Christopher J.
Abstract Aim C4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C3/C4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C3/C4 grass distributions. We consider multiple biogeographic regions of North America using a multisource database of over 40, 000 vegetation plots. Location The conterminous United States of America (USA). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C3 and C4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C3‐ or C4‐dominated states. Transitions between C3/C4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like Eastern Temperate Forests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C3/C4 abundance. Main conclusion Local ecological factors modify C3/C4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In Eastern Temperate Forests, for example, C4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.